Pediatric case of persistent hiccups associated with hypertrophic olivary degeneration - Arıcan, Pınar; Öztekin, Özgür; Çavuşoğlu, Dilek; Yılmaz, Sema Bozkaya; Ersen, Atilla; Dündar, Nihal Olgaç; Gençpınar, Pınar (The Turkish Journal of Pediatrics, 2020)
Background. Hypertrophic olivary degeneration (HOD) is a rare degenerative disorder that is thought to occur subsequent to a disruption of the dentate-rubro-olivary pathway. Case. We report a pediatric case of unilateral HOD presented with persistent hiccups and palatal tremor. Radiological examination of diaphragm was normal considering ultrasound and chest x-ray. On T2WI (weighted images) and Fluid Attenuated Inversion Recovery (FLAIR) images, hyperintense enlargement of the right inferior olivary nucleus was seen. No abnormal enhancement was detected on post-contrast scans and no evidence of restricted diffusion was seen. Susceptibility weighted imaging (SWI) sequences revealed a chronic hemorrhage involving the medulla oblongata and cerebellum. Cranial magnetic resonance imaging (MRI) findings were consistent with unilateral HOD. Palatal tremor and dentate-rubral tremor are frequent presentation of HOD, however to our knowledge persistent hiccups had not yet been reported in children with HOD. Conclusion. We highlight a pediatric case of unilateral HOD, which presented with persistent hiccups. Awareness of clinical and radiological findings of HOD is important to avoid misinterpretation as a mass lesion, an ischemic event, or a demyelinating disease and provide adequate management.
Keywords: children; hiccups; hypertrophic olivary degeneration